Non-prescription purchase of antibiotics during travel abroad among a general adult population in Norway: Findings from the seventh Tromsø Study - Gravningen, Kirsten Midttun; Field, Nigel; Blix, Hege Salvesen; Asfeldt, anne mette; Småbrekke, Lars (PLOS ONE, 2020)
Background - Non-prescription purchase of antibiotics is undesirable and has not recently been investigated in a representative population in a high-income low-use country during travel abroad. This study examined self-reported prevalence of antibiotic purchase abroad with and without prescription among participants reporting international travel in a general adult population in Norway, and the associations with socio-demographic, lifestyle and health factors. Methods - We analysed questionnaire-data from 19995 participants (10470 women) ≥40 years in the population-based Tromsø Study 7, 2015–2016. Data from the Norwegian Prescription Database were used to examine antibiotic use in Norway. We calculated adjusted odds ratios (AOR) for “travel abroad”, “any antibiotic purchase abroad”, and “antibiotic purchase abroad with” and “without prescription” using multivariable logistic regression. Results - Over half (55.0%, 95%CI 54.3–55.7%) participants reported travel abroad of >1 week duration in the past year. Travelers were more likely than non-travelers to be women (AOR = 2.02, 95%CI 1.42–2.88%) and report high education/income, childhood mostly lived abroad, healthy lifestyle, and good/excellent self-rated health. In total, 17904 travel episodes to 148 countries were reported. Altogether, 3.7% (95% CI 3.4%-4.1%) of travelers had purchased antibiotic abroad in the past year. Non-prescription purchase (1.5%, 95% CI 1.3–1.7) was associated with younger age, being female (AOR 1.41, 1.0–1.97), number of travels (reference: one episode, two: AOR = 1.82, 1.25–2.67, three: 2.60, 1.58–4.28, four: 3.10, 1.40–6.36 and ≥five: 4.70, 2.30–9.62), occurrences of diarrhoea (one: 2.42, 1.50–3.93 and ≥two: 3.08, 1.29–7.35), and antibiotic use in Norway in the past year (1.84, 1.29–2.62), whereas purchase with prescription (2.4%, 2.1–2.7) was associated with low income, growing-up abroad, recent hospital admission, additionally including number of travels/diarrhoea, and antibiotic use in Norway. Thailand (10.7%, 95% CI 7.8–14.3), ...